Ergonomic System Tennis Referee Chair Design - Ricky Andrianto; Irzal Irzal; Purwantono Purwantono; Delima Yanti Sari (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2020)
The referee chair is still up using the stairs by holding on to the leg of the chair or on the steps and facing the chair. After arriving on the chair, the referee must turn around to sit in the seat, this is very dangerous and can cause accidents because there is no safety to ride the referee's chair.Build and analyze the drive system in the design of an ergonomic tennis referee chair. This study uses an experimental method, which is included in the engineering and manufacturing of a machine. The testing process is carried out 5 times up and down with different loads, the results of 5 times the same test is 0.73m / minute, this is caused by the rotation generated by the same gearbox, so that the load does not affect the speed up and down the referee seat of the ergonomic system. From the results of the measurement known height of the early 56 cm and maximum height of 160 cm with a tilt 60 ̊. The maximum height that can be reached by the referee if calculated from a height of mor is 145.009246 cm. Kursi wasit masih dinaiki menggunakan tangga dengan berpegang pada kaki kursi atau pada anak tangga dan menghadap ke kursi. Setelah sampai diatas kursi, wasit harus memutar badan untuk duduk di tempat duduk, hal ini sangat berbahaya dan dapat menyebabkan kecelakaan karena tidak adanya pengaman untuk menaiki kursi wasit.Membangun dan menganalisis sistem penggerak pada rancang bangun kursi wasit Tenis sistem ergonomis. Penelitian ini menggunakan metode eksperimen, yakni termasuk kedalam rekayasa dan pembuatan suatu mesin. Proses pengujian dilakukan sebanyak 5 kali naik turun dengan beban yang berbeda, hasil dari 5 kali pengujian tersebut sama yaitu 0,73m/menit, hal ini disebabkan oleh putaran yang dihasilkan oleh gearbok sama, sehingga beban tidak mempengaruhi kecepatan naik dan turun kursi wasit sistem ergonomis. Dari hasil pengukuran diketahui tinggi mur awal 56 cm dan tinggi maksimal mur 160 cm dengan kemiringan 60̊. Tinggi maksimal yang dapat dicapai kursi wasit jika di hitung dari ketinggian mor adalah 145,009246 cm.